Successful Elite Sport Policies: An international comparison of the Sports Policy factors Leading to International Sporting Success (SPLISS 2.0) in 15 nations - de Bosscher, Veerle; Shibli, Simon; Westerbeek, Hans; van Bottenburg, Maarten (Meyer & Meyer Verlag, 2015)
How can nations improve their chances of winning medals in international sport? This book deals with the strategic policy planning process that underpins the development of successful national elite sport development systems. Drawing on various international competitiveness studies, it examines how nations develop and implement policies that are based on the critical success factors that may lead to competitive advantage in world sport. An international group of researchers joined forces to develop theories, methods and a model on the Sports Policy factors Leading to International Sporting Success (SPLISS). The book presents the results of the large-scale international SPLISS-project. In this project the research team identified, compared and contrasted elite sport policies and strategies in place for the Olympic Games and other events in 15 distinct nations. With input from 58 researchers and 33 policy makers worldwide and the views of over 3,000 elite athletes, 1,300 high performance coaches and 240 performance directors, this work is the largest benchmarking study of national elite sport policies ever conducted. The nations taking part in SPLISS are: • Americas: Brazil and Canada • Asia: Japan and South Korea • Europe: Belgium (Flanders & Wallonia), Denmark, Estonia, Finland, France, the Netherlands, Northern Ireland, Portugal, Spain, Switzerland • Oceania: Australia